2021
DOI: 10.48550/arxiv.2109.01020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the Relationship between (3200) Phaethon and (155140) 2005 UD through Telescopic and Laboratory Studies

Abstract: The relationship between the Near-Earth Objects (3200) Phaethon and (155140) 2005 UD is unclear. While both are parents to Meteor Showers, (the Geminids and Daytime Sextantids, respectively), have similar visible-wavelength reflectance spectra and orbits, dynamical investigations have failed to find any likely method to link the two objects in the recent past. Here we present the first near-infrared reflectance spectrum of 2005 UD, which shows it to be consistently linear and red-sloped unlike Phaethon's very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Suggested sources include the large B-type asteroid 2 Pallas (de León et al 2010) and, more likely, a collisional family in the inner asteroid belt (MacLennan et al 2021). The km-sized asteroid 2005 UD appears dynamically related to Phaethon (Ohtsuka et al 2006) and is coincidentally also a B-type object (Jewitt and Hsieh 2006), (although recent observations show dissimilarity in the near infrared; Kareta et al 2021). A dynamical relation to another kilometersized asteroid, 1999 YC, has also been proposed but is less certain, where 1999 YC is a neutral C-type spectrally distinct from the blue B-types Phaethon and 2005 UD (Kasuga and Jewitt 2008).…”
Section: Thermal Breakdown: (3200) Phaethonmentioning
confidence: 99%
“…Suggested sources include the large B-type asteroid 2 Pallas (de León et al 2010) and, more likely, a collisional family in the inner asteroid belt (MacLennan et al 2021). The km-sized asteroid 2005 UD appears dynamically related to Phaethon (Ohtsuka et al 2006) and is coincidentally also a B-type object (Jewitt and Hsieh 2006), (although recent observations show dissimilarity in the near infrared; Kareta et al 2021). A dynamical relation to another kilometersized asteroid, 1999 YC, has also been proposed but is less certain, where 1999 YC is a neutral C-type spectrally distinct from the blue B-types Phaethon and 2005 UD (Kasuga and Jewitt 2008).…”
Section: Thermal Breakdown: (3200) Phaethonmentioning
confidence: 99%
“…Ryabova et al (2019) asserted that 2005 UD is not a member of the Phaethon-Geminid complex based on their dynamical analysis over the last 5,000 years; however, Hanuš et al (2016), and more recently MacLennan et al (2021), suggested that the two objects might have separated from a common parent body a long time ago, approximately 10 5 years ago or, more likely, even before this epoch. On the contrary, Kareta et al (2021) argued that the similar spectral property is only by coincidence from the analysis of their near-infrared spectrum.…”
Section: Introductionmentioning
confidence: 99%